MEMAKNAI KEKERASAN ORANG MADURA DI PERANTAUAN: STUDI SOSIAL KEBERAGAMAAN MASYARAKAT MADURA DI SEMAMPIR JAWA TIMUR - Ahmad Fatoni (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2020)
Abstract The purpose of this study is to find out the forms of violence perpetrated by Madurese in Semampir and understand the extent to which religion as a socio-cultural system acts as a tool for social control. The research method that researcher use is a descriptive exploratory type of research. In this study, researcher wanted to explore further the social and cultural role of Madura as a trigger for various characters and acts of violence. The results showed that various acts of violence carried out by Madurese in Semampir were triggered by several factors. The most prominent factor is the exaggeration of self-esteem that is too excessive. Second, the process of interaction between Madurese in multi-ethnic overseas areas, such as in Semampir sub-district, does have socio-cultural characteristics that tend to be hard, both physically and psychologically. Third, the religious system of Madurese in Semampir is more dominated by ceremonial events so that it cannot be used as a tool for maximum social control. Keywords: Violence, Overseas Madura.